Desain Power System Stabilizer Berbasis Fuzzy Tipe-2 untuk Perbaikan Stabilitas Mesin Tunggal - I Made Ginarsa; Agung Budi Muljono; I Made Ari Nrartha; Osea Zebua (Jurnal Rekayasa Elektrika, 2018)
The growth of type-2 fuzzy logic system is penetrating electric power system field, especially on electric power system control sub-field in order to simplify the design of power system stabilizer (PSS). Traditionally, the function of conventional PSS is to damp rotor oscillation when a disturbance occurred due to transmission configuration or/and loading changes. However, the response of conventional PSS is slow with long settling time and high peak overshoot. To cover this problem, PSS based on type-2 fuzzy logic system (PFT2) is proposed. Simulation results show that the PFT2 is able to improve the stability of a single machine with 3 scenarios on transmission configuration and loading variation. The PFT2 gives shorter settling time for all scenarios and loading variation than the settling time of conventional PSS. Also, the peak overshoot of the PFT2 is smaller than the peak overshoot of the other competing PSS.